Ideological Resistance in Adrienne Rich’s “Diving into the Wreck” - Pokharel, Bishnu Prasad (Interdisciplinary Journal of Management and Social Sciences, 2023)
Adrienne Rich’s poem “Diving into the Wreck” takes an issue with woman identity. Questioning the ideologically preoccupied masculine stereotyping of woman, Rich envisions a world of independence and harmony in which male-female dichotomy ceases to exist. The poem symbolically states three distinct phases of journey to express protest and psychological victory over gender disparity in the male-controlled society. It raises the idea that the false stereotypical and socio-political framing about gender and its roles are inimical to maintaining equality in society. The main objective of the study is to infer how the patriarchal society generated a conventional system to keep women out of mainstream and also the way typical females planned to gain control of the vagaries of and ocentric culture. I used Tyson’s resistance theory as the main theoretical tool to analyze and interpret the poem. This theoretical stratagem preserves the literature related to the struggle for freedom and impartiality. This article argues that the poem challenges the institutional apparatuses that naturalize women’s role and identity and advocates to establish gender impartiality in the society. I contend that this poem is the bedrock for the establishment of independence. The overall inference of the paper is that the protracted prejudice that leads to life-threatening exploitation creates revolt through literature and leads to plausible upheaval in society. Thus, it is discernible that literature, far from being the innocent figment of imagination, represents a subtle voice of resistance against exploitation and prejudice.